Extractable and non‐extractable polyphenols from blueberries modulate LPS‐induced expression of iNOS and COX‐2 in RAW264.7 macrophages via the NF‐κB signalling pathway. (29th December 2015) - Cheng, Anwei; Han, Caijing; Fang, Xixiu; Sun, Jinyue; Chen, Xiangyan; Wan, Fachun
Abstract: BACKGROUND: Plant polyphenols are rich in blueberries that have a wide range of properties beneficial to human health. There are two types, according to the solubility of polyphenols, which were defined as extractable polyphenols (EPP) and non‐extractable polyphenols (NEPP), respectively. At present, in most of reports, 'total polyphenol' refers only to EPP excluding NEPP. In this paper, the effects of EPP and NEPP on lipopolysaccharides (LPS) induced production of nitric oxide (NO) and gene expression of inducible NO synthase (iNOS) and cyclooxygenase‐2 (COX‐2) in RAW264.7 cells via nuclear factor‐κB (NF‐κB) signalling pathway were compared. RESULTS: The results showed that EPP and NEPP from blueberries significantly inhibited the LPS‐induced production of NO and gene expression of iNOS and COX‐2 in cells. The constitutive level of p65 sub‐unit of NF‐κB was obviously detected after the treatments with EPP or NEPP. By contrast, the level of phosphorylated p65 (P‐p65) was strongly inhibited by EPP or NEPP. EPP had a stronger inhibition on the gene expression of iNOS and COX‐2 than that of NEPP. CONCLUSION: These findings of inhibition of iNOS and COX‐2 mRNA expression through the suppression of NF‐κB suggest that EPP and ENPP from blueberries have significant anti‐inflammatory effect and may be a potential medicine. © 2015 Society of Chemical Industry